POSSIBILITIES OF USING DIGITAL MARKETING TECHNOLOGIES IN INCREASING THE ATTRACTIVENESS OF TOURISM SERVICES IN BUKHARA REGION (Marketing Journal, 2025)
This article examines the potential of using digital marketing technologies to enhance the appeal of tourism services in the Bukhara region. The study analyzed modern digital marketing methods, such as social media marketing, search engine optimization (SE O), content marketing, and influencer marketing. The results showed that the flow of local and international tourists can be significantly increased by implementing digital marketing strategies in the Bukhara region.
Keywords: digital marketing; tourism services; social media marketing; SEO; content marketing; video marketing; mobile marketing; tourism destination